2014
DOI: 10.1128/jvi.01571-13
|View full text |Cite
|
Sign up to set email alerts
|

Inosine-Mediated Modulation of RNA Sensing by Toll-Like Receptor 7 (TLR7) and TLR8

Abstract: i RNA-specific adenosine deaminase (ADAR)-mediated adenosine-to-inosine (A-to-I) editing is a critical arm of the antiviral response. However, mechanistic insights into how A-to-I RNA editing affects viral infection are lacking. We posited that inosine incorporation into RNA facilitates sensing of nonself RNA by innate immune sensors and accordingly investigated the impact of inosine-modified RNA on Toll-like receptor 7 and 8 (TLR7/8) sensing. Inosine incorporation into synthetic single-stranded RNA (ssRNA) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…As shown in Figure 5 , miR-224-5p mut2 AMO is more stable than the native miR-224-5p and miR-224-5p mut1 AMOs, and displayed the strongest TLR7 inhibitory activity. Given that 2′OMe RNAs have a strong affinity to TLR7 ( 13 ), it is reasonable to assume that the rules regulating their TLR7 activity are similar to that of immunostimulatory ssRNA, and that structure has an impact ( 20 21 , 44 ). We have previously shown that immunostimulatory motifs embedded in RNA with double-stranded regions were more potent activators of TLR8 ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 5 , miR-224-5p mut2 AMO is more stable than the native miR-224-5p and miR-224-5p mut1 AMOs, and displayed the strongest TLR7 inhibitory activity. Given that 2′OMe RNAs have a strong affinity to TLR7 ( 13 ), it is reasonable to assume that the rules regulating their TLR7 activity are similar to that of immunostimulatory ssRNA, and that structure has an impact ( 20 21 , 44 ). We have previously shown that immunostimulatory motifs embedded in RNA with double-stranded regions were more potent activators of TLR8 ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the changes in RNA secondary structures associated with inosine are detected through TLR7 and TLR8. These changes also lead to an increase in TNF-α production, which would mean that inosine serves as a molecular pattern to be recognized in the phagocytosed RNA, as these receptors are mainly expressed by antigen-presenting dendritic cells ( 78 ).…”
Section: Viral Rna Modificationsmentioning
confidence: 99%
“…More recently, researchers also determined that the RNA editing phenomenon of adenosine-to-inosine conversion enhances TLR7/8 activation. In this experiment, TLR7 sensing of ssRNA was enhanced in inosine-modified viral RNA (Sarvestani et al, 2014). The cooperative role between TLR7 and TLR8 is also an important part of the mechanism that results in an IFN response to ssRNA.…”
Section: Rna Nucleic Acid Sensing In Viral Immunology and Autoimmunitymentioning
confidence: 99%